Challenges and Critical Success Factors for Rural Agrarian Reforms in Limpopo Province, South Africa - Ndlovu, Wiseman; Mwale, Marizvikuru; Zuwarimwe, Jethro (Universitas Muhammadiyah Yogyakarta, 2021)
The need for rural land agrarian reforms has reached heightened levels in South Africa in recent years. Resultantly, the communal land use effectiveness is questioned due to persistent poor performance and declining agricultural output that fails to address rural poverty and food insecurity. This is one of the major causes of why South Africa's rural economies are generally characterized by stagnant economic growth. This points to deep-rooted and unique challenges that need urgent attention if meaningful support and resilience systems are to be built for rural agrarian land reforms to be realized. The present study investigated challenges and characterized factors that lead to the prosperity of rural agricultural projects in communal land ownership. An exploratory study design was followed, and the data was collected using interviews and focus group discussions from communal farmers and key informants. Data were analyzed thematically with the aid of Atlas. Ti version 8.1.4. â€œInformation challengesâ€ and â€œwater scarcityâ€ describe some of the common challenges faced by rural farmers. Six critical success factors were identified and found to be related. â€œEffective project management and controlâ€ and â€œimproved support from and partnership with local community stakeholdersâ€ are success factors that, if targeted first, could address most challenges faced in rural agrarian reforms. The results suggest that partnership with the private sector can help farmers commercialize and move swiftly towards agro-processing. Identified threats and successes must be prioritized in designing and formulating region-specific rural agrarian support programs for communal farmers.